Comparative Legal Responses to Illicit Wildlife Trade in Bangladesh and India: Indigenous vs. Extraneous Approaches - Nower suvra , Anika; Ontar, Morshed Hossain (Fakultas Hukum Universitas Lampung, 2024)
This research examined the legal responses to illicit wildlife trade in Bangladesh and India, focusing on how these countries harmonized their domestic laws with international obligations under the Convention on International Trade in Endangered Species (CITES). It assessed the effectiveness of Bangladesh's legal framework against wildlife trafficking and compared it to India’s advancements, particularly the Indian Wildlife Protection Amendment Act of 2022. Utilizing qualitative and doctrinal methods, the research reviewed primary and secondary sources, including statutes and international agreements. While Bangladesh faced significant challenges in enforcement and effectiveness, India strengthened its wildlife protection through stricter penalties and enhanced compliance with CITES. The research advocated for Bangladesh to adopt similar legislative reforms and improve enforcement mechanisms to better protect biodiversity and fulfill international obligations.